Analysis of Digital Literacy and School Culture's Impact on Primary School Learning Quality - Ulin Nafiah; Sri Utaminingsih; Gunawan Setiadi (Pascasarjana Universitas KH. Abdul Chalim, 2026)
This study examines the relationship between digital literacy, school culture, and the quality of learning in elementary schools. With technology becoming a crucial aspect of modern education, digital literacy and a positive school culture are increasingly recognized as vital components of effective learning. The primary aim of this research is to assess how these two factors influence the overall quality of learning at SD Negeri Gugus RA Kartini, Trangkil. The research adopts a quantitative approach with a correlational design, using a digital literacy questionnaire, a school culture questionnaire, and a learning quality questionnaire administered to 72 teachers and staff. The study's hypothesis proposes that both digital literacy and school culture have a significant impact on learning quality. The results reveal that although digital literacy and school culture are rated as good, neither variable has a significant direct effect on learning quality when tested partially or simultaneously. However, both factors still contribute moderately to explaining variations in learning outcomes. These findings suggest that improving learning quality cannot rely solely on enhancing digital literacy or fostering a positive school culture; it must also consider other factors such as teacher pedagogical competence, learning design, and parental support. The study implies that future educational strategies should integrate digital literacy within a broader pedagogical framework and strengthen school culture in a consistent and collaborative manner to realize its potential impact on learning quality.